Analysis Model of Giant Prawns Population (Macrobrachium rosenbergii) in Estuary Edge of Sembakung Waters, Nunukan, Indonesia - Agus Indarjo; Gazali Salim; Christine Dyta Nugraeni; Lukman Yudho Prakoso; Permana Ari Soejarwo; Rukisah Rukisah; Yen Thi Hong Pham; Achmad Daengs GS; Hariyadi Hariyadi; Abdul Jabarsyah (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight • The sex ratio of giant prawns in the waters of fe- male groceries is 3 times higher than that of males. • The growth characteristic of male and female   giant   prawns   is   negative   allometry, but the male and female body shapes are fat. • Total   mortality, capture mortality, catch rate, male prawns are higher than females. • The male infinitive growth is longer than the female,but the female's growth rate is faster than male.